Pengaruh Profitabilitas, Likuiditas, Aktivitas Dan Leverage Terhadap Nilai Perusahaan - Rinny Lupitasari; Wahyu Kurniawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims to determine the effect of profitability, liquidity, activity and leverage on firm value. The population is Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2021 financial reports. The sample was determined by purposive sampling technique with certain criteria and a sample of 45 companies was obtained. Th¬is study tested the data using Smart Partial Least Square (SmartPLS) version 3.2.9. Based on the results of the study it can be concluded that profitability and activity have a positive and significant effect on firm value, liquidity has a negative and significant effect on firm value, and leverage has no effect on firm value